(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cadmium oxide nanoparticles are synthesized by various methods. This article summarizes the literature on the various method of synthesis of cadmium oxide nanoparticles. Investigation has been carried out across the world in order to synthesis and application of cadmium oxide nanoparticles.